From Childhood to Adulthood: A Systematic Review of the Evolution, Diagnosis, and Management of PFAPA Syndrome - Mohammad, Adawi; Adawi, Amin; Abozaid, Said (Archives of Clinical and Biomedical Research, 2025)
Adult PFAPA (Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Adenitis) syndrome represents an underrecognized yet significant autoinflammatory disorder. Traditionally considered a pediatric condition, recent literature illustrates its persistence and emergence in adulthood. This systematic review synthesizes current evidence on the clinical phenotype, diagnostic challenges, and therapeutic strategies for adult PFAPA. The syndrome in adults often mirrors pediatric presentations but may exhibit increased arthralgia, myalgia, and diagnostic delay. Distinguishing adult PFAPA from other periodic fever syndromes is crucial, given overlapping clinical features and often inconclusive genetic testing. Despite the lack of defined biomarkers, a phenotype-driven approach and recognition of episodic fever with aphthous ulcers and cervical lymphadenopathy remain vital for diagnosis. Treatment responses vary, with corticosteroids showing efficacy, while tonsillectomy and IL-1 blockers like anakinra may benefit selected patients. The review highlights the need for standardized diagnostic criteria, improved awareness among clinicians, and further research into the genetic and immunological underpinnings of adult PFAPA.